170 THE EFFECTS OF MEDICATIONS AND VENTILATOR MANAGEMENT ON WEIGHT GAIN OF EXTREMELY LOW BIRTHWEIGHT INFANTS IN THE PERI-EXTUBATION PERIOD. (1st January 2005) - Coulter, D. M.; Moyer-Mileur, L. M.
Abstract : Both respirator support and medications used to facilitate extubation of premature babies potentially affect weight gain. We reviewed the charts of 100 pts whose birth weights were ≤1 kg and who had received full enteral feedings for at least 7 days before and after extubation. We determined the effects of ventilator support (SIMV, NCPAP) and medications (caffeine, theophylline, dexamethasone) on weight gain normalized for weight and caloric intake (gm/kg/Kcal/d) for the 7 days prior to and after extubation, excluding the day of extubation, a total of 1400 observations. (Table ) Dexamethasone therapy dramatically reduced growth, a result previously reported. Methylxanthines had absolutely no effect on calorie utilization for growth. NCPAP caused a 20% reduction in growth, a result that was statistically insignificant. The known imprecision of daily weights in small babies may mask a clinically significant difference in growth of small babies on NCPAP. Despite the use of dexamethasone and NCPAP in the post-extubation period, extubation resulted in a small increase in weight gain. Prolonging mechanical ventilation in these tiny babies carries known risks and does not promote growth.